2015
DOI: 10.1152/ajpendo.00030.2015
|View full text |Cite
|
Sign up to set email alerts
|

Administration of 17β-estradiol to ovariectomized obese female mice reverses obesity-hypertension through an ACE2-dependent mechanism

Abstract: nikouris F, English VL, Cassis LA. Administration of 17␤-estradiol to ovariectomized obese female mice reverses obesityhypertension through an ACE2-dependent mechanism. Am J Physiol Endocrinol Metab 308: E1066 -E1075, 2015. First published April 14, 2015 doi:10.1152/ajpendo.00030.2015-We recently demonstrated that female mice are resistant to the development of obesity-induced hypertension through a sex hormone-dependent mechanism that involved adipose angiotensin-converting enzyme 2 (ACE2). In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 44 publications
3
59
0
1
Order By: Relevance
“…The difference in body composition between pre‐ and postmenopausal women clearly indicates the beneficial effect of estrogens in adipose biology. Studies have shown that administration of estradiol to ovariectomized rats or mice reduces obesity (21), supporting the hypothesis that estrogens are responsible for tightly regulating body weight in women. In addition to favorable effects on adipose tissue, estrogens also attenuate hyperphagia through ER‐a (22,23) and through actions in the central nervous system (24, 25), all culminating in weight loss.…”
mentioning
confidence: 80%
“…The difference in body composition between pre‐ and postmenopausal women clearly indicates the beneficial effect of estrogens in adipose biology. Studies have shown that administration of estradiol to ovariectomized rats or mice reduces obesity (21), supporting the hypothesis that estrogens are responsible for tightly regulating body weight in women. In addition to favorable effects on adipose tissue, estrogens also attenuate hyperphagia through ER‐a (22,23) and through actions in the central nervous system (24, 25), all culminating in weight loss.…”
mentioning
confidence: 80%
“…Blood pressure was measured by radiotelemetry during week 16 as previously described 41 . Briefly, anesthetized (isoflurane) male and female mice fed a HF were implanted with carotid artery catheters and telemetry devices (Data Sciences, Inc., St. Paul, MN) during week 15 of HF feeding, allowed 10 days to recover.…”
Section: Methodsmentioning
confidence: 99%
“…Ovariectomized (OVX) mice have an increased susceptibility to obesity and its complications including adipose inflammation, insulin resistance, and hepatic steatosis (You et al, 2004;Kaaja, 2008;Hong et al, 2009;Ludgero-Correia et al, 2012). Conversely, estrogen replacement decreases body weight and blood pressure and protects against fatty liver and insulin resistance (Zhu et al, 2013;Wang et al, 2015). Our previous study demonstrated that ginseng prevented obesity through angiogenesis inhibition (Lee et al, 2013(Lee et al, , 2014; however, these results were obtained using male mice and db/db mice.…”
Section: Introductionmentioning
confidence: 92%